Summary of past experimental work in sheep and goat management, breeding and health at National Animal Husbandry Research Station, Naivasha, Kenya - Chemitei, V.C.C. (Food and Agriculture Organization of the United Nations, 1973)
A result summary was made on past experimental work in sheep and goat management breeding and health at National Animal Husbandry Research station at Naivasha and Oi’Magogo. The report indicated greasy wool yields from 1954 to 1972 for merino sheep and Awassi ewe’s lactation from 1964 to 1968. It also included haemonchiasis research project at Naivasha and Kabete 1969 – 1970. Observations on feeding trial for Merino at Ol’Magogo. Weaning lambs performance and subsequent lambing and wool performance at Naviasha and Ol’ Magogo 1970 have been reported in the summary. Fleece weight pre and post weaning weight, live weight, mutton production and reproductive performances were compared for Merino, Romney Marsh and Corriedale sheep at Naivasha and Ol’Magogo Research stations.